Respuesta :

Answer:

For this expression, you will have to use the distribution property to get your answer.


First, distribute the 4 to the x and -1

[tex]4(x)=4x[/tex]

[tex]4(-1)=-4[/tex]


[tex]4x-4-3(x+2)[/tex]

Now do the same with the -3, x and 2

[tex]-3(x)=-3x[/tex]

[tex]-3(2)=-6[/tex]


[tex]4x-4-3x-6[/tex]

Now combine like terms to get your final answer

[tex]4x-3x=x[/tex]

[tex]-4-6=-10[/tex]


Thus, your solution is: x - 10


Step one: 4(x-1)-3(x+2)=0        (set equal to zero)

Step two: 4x-4-3x-6=0            (multiply numbers on the outside to inside of "( )")

Step three: x-10=0                   (combine like terms)

Step four: 0+10=10, x=10         (inverse operation)

Answer: x=10